Tension-type headache and low back pain reconsidered - Astrup, Jens; Gyntelberg, Finn (Frontiers in Neurology, 2022)
The natural history and clinical course of tension-type headache and non-specific low back pain are reconsidered. By closer examination, these two conditions appear to share several specific clinical features. Both are muscular pain conditions along the spine, they have a preponderance in women, they may occur spontaneously or follow a trivial traumatic incident, and they both have a high risk of chronicity. The affected muscles are tender with tender points. EMG indicates diffuse hyperactivity and abnormal activation pattern, and motor control of the affected muscles and adjacent muscle groups is discoordinated. These shared features suggest analogous pathophysiology involving the neuromotor control of affected and adjacent muscle groups in the cervical and lumbar regions, respectively. As recently suggested for the whiplash disease, we suggest the term spinal dyssynergia for this specific pattern of pathology. This suggestion provides a new perspective for the understanding of these diseases by placing their cause within the central nervous system and not in the spine or spinal musculature. This perspective warrants further clinical, neurophysiological, and neuropharmacological studies of this ‘family’ of common yet poorly understood clinical muscular pain conditions along the spine.